Comparative survey on pupils’ beliefs of mathematics teaching in Finland and Ukraine - Pehkonen, Erkki; Rakov, Sergey (Teaching Mathematics and Computer Science, 2005)
The focus of this comparative survey was the following research question: What are the differences and similarities in pupils’ beliefs in mathematics between Finland and Ukraine? Data were gathered with the help of a questionnaire. The questionnaire consists of 32 structured statements about mathematics teaching for which the pupils were asked to rate their beliefs on a 5-step scale. The Finnish sample comprised 255 pupils, and the Ukrainian sample 200 pupils. Our data has been gathered with a non-probabilistic convenience sampling. The main results of our survey are, as follows: Generally, pupils’ beliefs of mathematics teaching and learning in Finland and Ukraine are rather far from similar. An investigation of the differences between pupils’ answers across the two countries also showed beliefs that are characteristic for each country. For pupils in Finland, the characteristic beliefs seem to be, as follows: the value of strict discipline, working in small groups, and the idea that all understand. For pupils in Ukraine, the most characteristic might be the following beliefs: the use of learning games, the emphases of mathematical concepts, and teachers’ explanations.